Diversity of piroplasmids in wild animals in Brazil: a review - Calchi, Ana Cláudia [UNESP]; Soares, João Fabio; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (FapUNIFESP (SciELO), 2025)
The study of the diversity of tick-borne agents in wild animals enables a better understanding of the distribution of pathogens in the country, the identification of potential reservoirs for these agents, the mapping of possible infection hotspots, the implementation of local fauna management, and the development of species conservation strategies, as well as the creation of disease control and prevention strategies. Piroplasmids are apicomplexan protozoa that primarily infect blood cells of vertebrates and can cause diseases in animals and humans. In Brazil, several studies have identified a wide diversity of piroplasmids in different species of wild animals. This review article aims to compile these studies, with an emphasis on the species detected according to host orders and families, the diagnostic methods used, the occurrence of clinical signs, and the distribution of these agents across the country. It also aims to review the phylogenetic topology of piroplasmids by including the new species and clades detected in the country.